Surgical Accuracy of an Early Intervention Knee Implant Instrumentation System - Lowry, Mike; Buza, John; Liu, James; Rosenbaum, Heather; Lavery, Jessica; Bosco, Joseph; Walker, Peter S. (The Journal of Knee Surgery, 2018)
Accuracy of component and limb alignment are critical parameters for the long-term success of unicompartmental knee implants. In this study, we performed a laboratory evaluation of an instrumentation system which was designed for an early intervention (EI) type of unicompartmental knee. The accuracy of fit was evaluated by implanting in 20 sawbones full leg models. The overall alignment of the limb was compared pre- and postoperatively. The accuracy of placement of each component on its bone was measured. The mean overall alignment angle in the frontal plane was within 1° of target with less than 1° standard deviation. The components were positioned in frontal and sagittal planes with maximum errors of 2°. The angular accuracy was better than in studies reported in the literature for manual instruments, and almost approached the accuracy of computer-assisted systems. The position of the femoral component in the recess was within 1 mm in most cases but the sagittal flexion angle was variable with a standard deviation of 6°. Evaluation of a surgical technique in this way was a valuable method for determining accuracy and for highlighting any deficiencies in the system which could then be corrected.
Keywords: early intervention knee; unicompartmental knee; knee alignment; surgical technique for knee implants; accuracy of surgical technique